2004
DOI: 10.15666/aeer/02143163
|View full text |Cite
|
Sign up to set email alerts
|

Migration of Fishes in Romanian Danube River (Nº 1)

Abstract: A Ab bs st tr ra ac ct t. . Present review paper tries to show the main aspects of migration of fishes in Romanian sector of Danube River. The Danube River has a large hydrographical basin, being the second largest river in Europe. The main channel flows trough seven European countries. There are many species of fish that annually or seasonally migrate either for reproduction or feeding in different areas of Danube and its main tributaries. K Ke ey yw wo or rd ds s: : migration, fish, capture dynamic, Danube, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
16
0
2

Year Published

2009
2009
2019
2019

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 3 publications
0
16
0
2
Order By: Relevance
“…Confidence intervals overlapping 1 indicate use in proportion to availability. neau and Scarnecchia 2002;Ciolac 2004). However, common carp spawning behavior was observed in both flowing and impounded areas of the Fox River.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Confidence intervals overlapping 1 indicate use in proportion to availability. neau and Scarnecchia 2002;Ciolac 2004). However, common carp spawning behavior was observed in both flowing and impounded areas of the Fox River.…”
Section: Discussionmentioning
confidence: 99%
“…In many systems, common carp congregate in shallow, vegetated areas during spring spawning, disperse during summer, and congregate again in large groups at overwintering sites (Johnsen and Hasler 1977;Otis and Weber 1982;Penne and Pierce 2008;Jones and Stuart 2009). Some studies have described distinct upstream spawning migrations (Rodriguez-Ruiz and Granado-Lorencio 1992;Bonneau and Scarnecchia 2002;Ciolac 2004), whereas others have reported that common carp do not migrate and only exhibit localized movements (Reynolds 1983;Lubinski et al 1986). Local habitat characteristics may influence the movement patterns of common carp, with movements being greater in systems where critical habitats (e.g., spawning and overwintering areas) are distantly separated (Northcote 1984;Schlosser 1991).…”
mentioning
confidence: 99%
“…Having over‐wintered in deep, slow‐moving areas of the main channel, S. glanis move at the end of March–April, when temperatures are 8–10 °C (Berg 1949; Shikhshabekov 1978) undertaking short‐distance migrations upstream to spawning grounds (Lelek 1987). In the lower River Danube, this migration is reported to take place in February and March at water temperatures of 4–6 °C (Ciolac 2004). In Central Europe, this migration generally takes place from the end of March to the beginning of April and in Eastern Europe, from the end of May until June.…”
Section: Reproductionmentioning
confidence: 99%
“…Alosa pontica is very sensitive to water temperature, water turbidity, and the amplitude of water level oscillations. High turbidity or low water levels have a strong negative impact on migration (Banarescu 1964;Ciolac 2004). There is an extremely interesting detail about this species: although not large in size, by migration time it becomes extremely abundant, making it economically very attractive.…”
Section: Family Clupeidaementioning
confidence: 99%
“…The density and dispersal of the carp population in the Danube depends on the way migration for reproduction occurs in relation to water level (floods) and temperature, which must be as high as 12-15˚C, usually by May. It returns to the main river once the eggs have been laid in the flooded area (Ciolac 2004).…”
Section: Family Cyprinidaementioning
confidence: 99%